EXPLORING THE PARADOXES OF TOURISM: HOW MEMORABLE EXPERIENCES, CITY BRANDING, AND DESTINATION IMAGE INFLUENCE REVISIT INTENTIONS? - Astuti, Widji; Natsir, Mokhamad; Elmas, Muhammad (Faculty of Economic and Business, University of Pasundan, 2025)
This study addresses a critical gap in tourism literature by examining how memorable tourism experiences, city branding, and destination image collectively influence revisit intention through tourist satisfaction in Batu City Tourism Village. Using Structural Equation Modeling (SEM) on data from 155 visitors surveyed within six months of their visit, the results show that while memorable experiences and city branding enhance satisfaction, they do not directly impact revisit intention. In contrast, destination image significantly influences revisit intention, highlighting its critical role in shaping tourist behavior. The findings challenge the assumption that positive experiences and strong branding alone ensure return visits, emphasizing the complexity of tourist decision-making. Additionally, tourist satisfaction mediates these relationships but proves insufficient on its own to guarantee revisit intention. These insights underscore the need for dynamic tourism strategies that prioritize enhancing destination image while offering compelling reasons for tourists to return, ensuring alignment with evolving preferences and expectations.